Serotonin/GABA receptors modulate odor input to olfactory receptor neuron in locusts - Lv, Mingyue; Xu, Xiao; Zhang, Xinyang; Yuwen, Bo; Zhang, Long (Frontiers in Cellular Neuroscience, 2023)
Serotonin (5-hydroxytryptamine; 5-HT) and GABA (γ-aminobutyric acid) are involved in the regulation of behaviours in central nerve system. However, it remains unclear whether and how their modulation of olfaction in the peripheral nervous system. One 5-HT receptor sequence (Lmig5-HT2) and one GABA receptor sequence (LmigGABAb) were identified in locust antennae by transcriptome analysis and polymerase chain reaction experiments. In situ hybridisation localised Lmig5-HT2 to accessory cells, while LmigGABAb was localised to olfactory receptor neurons (ORNs) in locust chemosensilla. Single-unit electrophysiological recordings combined with RNA interference (RNAi) experiments indicated ORNs of locusts with knockdown of Lmig5-HT2 (ds-Lmig5-HT2) and LmigGABAb (ds-LmigGABAb) to some odours had significantly higher responses than wild-type and control locusts in the dose-dependent responses. Moreover, the gaps between responses of ORNs of RNAi ones and those of wild- type and ds-GFP enlarged with increase of concentrations of odours. Taken together, our findings suggest that 5-HT, GABA, and their receptors exist in the insect peripheral nervous system, and that they may function as negative feedback to ORNs, and contribute to a fine-tuning mechanism for olfaction in the peripheral nervous system.